Pengaruh Guncangan Makroekonomi terhadap Integrasi Pasar Modal di ASEAN-5 - Iyan Anriansyah; Hermanto Siregar; TB Nur Ahmad Maulana (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2018)
This study aim is to analyze the effects of the shocks of the macroeconomic variable on the capital market integration in ASEAN 5 represented by stock price indexes. The stock price indexes used included Indonesia (IHSG), Malaysia (KLCI), Singapore (STI), Thailand (SETI) and Philippines (PSEI), and the macroeconomic variables used in Indonesia included the industrial production (IPI), inflation (INFI), interest rate (SBI) and exchange rate (KURSI). The method used was the analysis of VAR/VECM using impulse response function (IRF), forecast error Variance decomposition (FEVD) and granger causality of the study period of 2001-2016. The results showed that IHSG and STI had a two-way causality and had a unidirectional causal relationship to PSEI, KLSE and SET. Shocks of inflation, interest rates and exchange rates had a negative correlation with the Index of the ASEAN 5, while industrial production shocks had a positive relationship. IHSG and KLSE were more influenced by the inflation rate in Indonesia while PSEI, STI and SET were more affected by interest rates in Indonesia.Keywords: composite index, ASEAN 5, macroeconomic variables, VAR /VECM, granger causality